2018
DOI: 10.1016/j.amj.2017.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Does Medical Staffing Influence Perceived Safety? An International Survey on Medical Crew Models in Helicopter Emergency Medical Services

Abstract: Our survey shows a wide variety of medical staffing models in HEMS and indicates that these differences are mainly related to medical competencies and the availability of an assistant in the medical cabin. The responses suggest that differences in medical staffing influence perceived flight and patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…According to the reports of some studies, there is a training syllabus for air ambulance personnel in some countries, including Norway, the United States, and England, consistent with their national standards,[ 39 ] as their knowledge and skill are vital for providing high quality and safe services. [ 40 41 42 ] Lack of training and personnel's incorrect perception of conditions of physical changes affect the patient physiology during flight, while also leading to the severity of injuries and side effects such as bleeding, hemothorax, and pneumothorax.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the reports of some studies, there is a training syllabus for air ambulance personnel in some countries, including Norway, the United States, and England, consistent with their national standards,[ 39 ] as their knowledge and skill are vital for providing high quality and safe services. [ 40 41 42 ] Lack of training and personnel's incorrect perception of conditions of physical changes affect the patient physiology during flight, while also leading to the severity of injuries and side effects such as bleeding, hemothorax, and pneumothorax.…”
Section: Resultsmentioning
confidence: 99%
“…In general, there is disagreement on the ideal combination of the medical group,[ 15 ] though studies revealed that the presence of a physician improves the quality of the services. [ 39 45 ] Sahebi et al . suggested that comprehensive training programs should be implemented for effective management of the air emergency process during disasters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the necessary condition for a successful ME improvement is additional training of the MT crew's specialists to constantly increase their qualifications. 21,22 The decreasing of MT crews is another important and often unresolved problem. Important problems are bad roads, the fuel limit, and non-working vehicles.…”
Section: Current Problems In Health Crew Creationmentioning
confidence: 99%
“…But it must be remembered that the correct chosen transport remains necessary to avoid the complications in time and after transportation. [22][23][24] For example, the height rising in aircraft flight leads to the atmosphere pressure reducing that may cause hypoxia and the gas expansion in the patient's body cavities, 25,26 which can cause dangerous physiological reactions for the patient. 27 One more is the undesirable usage of aircraft for ME purposes in places of biological, chemical, or nuclear weapons usage because of the possible infection or poisoning of the crew.…”
Section: Current Problems In Health Crew Creationmentioning
confidence: 99%